Effect of temperature on growth, photosynthesis and biochemical composition of Nannochloropsis oceanica, grown outdoors in tubular photobioreactors - Carneiro, M. (2022)
Since temperature is an important factor affecting microalgal growth, photosynthetic rate and biomass composition, this study has accordingly focused on its effects on biomass yield and nighttime biomass loss, as well as photochemical changes, using Nannochloropsis oceanica as model species, grown in two outdoor 50-L tubular photobioreactors (PBR). In two independent trials, cultures were subjected to a diurnal light:dark cycle, under a constant temperature of 28 degrees C and, on the second trial, at 18 degrees C. Changes in culture performance were assessed by measuring growth, lipid and fatty acid composition of the biomass in both morning and evening. Our results revealed that N. oceanica shows a wide temperature tolerance with relevant nighttime biomass loss, that decreased at lower temperatures, at the expenses of its daily productivity. Fluorescence measurements revealed reversible damage to photosystem II in cells growing in the PBR under optimal thermal conditions, whereas microalgae grown at suboptimal ones exhibited an overall lower photosynthetic activity. Lipids were partially consumed overnight to support cell division and provide maintenance energy. Eicosapentaenoic acid (EPA) catabolism reached a maximum after the dark period, as opposed to their saturated counterparts; whereas lower temperatures led to higher EPA content which reached the maximum in the morning. These findings are relevant for the production of Nannochloropsis at industrial scale.